Feasibility Study of Stress Measurement in Prestressing Tendons Using Villari Effect and Induced Magnetic Field - Changbin Joh; Jung Woo Lee; Imjong Kwahk (International Journal of Distributed Sensor Networks)
This paper investigates experimentally the feasibility of estimating the stress in the prestressing tendons of prestressed concrete bridges using the magnetic field induced by an electromagnet and the Villari effect in which the magnetic susceptibility or permeability of a ferromagnetic material changes when subjected to a mechanical stress. The test results show the good linearity between the stress in the prestressing tendon and the induced magnetic flux density within the practical stress range of the tendons. In addition, the induced magnetic flux density in the tendon appears to depend on the intensity of the electromagnet and the distance between the electromagnet and the tendon regardless of the concrete cover. Accordingly, although further studies are needed for practical applications, the stress in the prestressing tendon of a prestressed concrete bridge can be estimated by measuring the induced magnetic flux density generated in the tendon and by using the linear relationship between this induced magnetic flux density and the stress in the prestressing tendon.